Students’ beliefs on translation strategy in learning German language - Bong, Tze Ying; Ang, Lay Hoon; Hazlina Abdul Halim,; Majtanova, Miroslava (Penerbit Universiti Kebangsaan Malaysia, 2018)
The growing number of research studies on the application of translation in language learning has shown that this topic is getting popular among education research groups. It is a challenging task for a non-native speaker to learn a foreign language, especially if the grammar of the student’s dominant language is different from the grammar of the foreign language. Among the many methods employed in foreign language learning, the translation method continues to remain a controversial issue. This study is primarily designed to understand the role of translation for non-native speakers in the learning of German as a foreign language, specifically in ascertaining students’ beliefs about using translation in their studies of the foreign language, and to find out the learning strategies, which involve translation. A total of 60 Malaysian undergraduates studying German as a foreign language in a public university participated in this study. Data collection was carried out using a questionnaire on the use of translation in learning German language and semi-structured interview. It can be concluded from the findings of the study that the majority of the participants believed that the use of translation is a helping strategy for learning the German language. Although a small number of the participants preferred to learn the German language without using translation, they agreed that translation really helped to develop their learning strategy, especially in a situation where they did not understand the German language spoken by their lecturer in class. It is hoped that the findings of this study will shed light on the use of translation in teaching and learning the German language.